2017
DOI: 10.3847/1538-4357/835/2/275
|View full text |Cite
|
Sign up to set email alerts
|

Flux and Polarization Variability of OJ 287 during the Early 2016 Outburst

Abstract: The gamma-ray blazar OJ 287 was in a high activity state during December 2015 -February 2016 Coinciding with this high brightness state, we observed this source for photometry on 40 nights in R-band and for polarimetry on 9 epochs in U BV RI bands. During the period of our observations, the source brightness varied between 13.20 ± 0.04 to 14.98 ± 0.04 mag and the degree of polarization (P ) fluctuated between 6.0 ± 0.3% and 28.3 ± 0.8% in R-band. Focusing on intra-night optical variability (INOV), we find a du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Only 31 and 24 objects showed short-term variability in at least one window in W 1 and W 2 bands respectively while only 17 objects showed short-term variability in both W 1 and W 2 bands. We also estimated the duty cycle (DC; see Rakshit et al 2017b) i.e. the fraction of time when an object is variable in Table 1.…”
Section: Short-term Variability Amplitudementioning
confidence: 99%
“…Only 31 and 24 objects showed short-term variability in at least one window in W 1 and W 2 bands respectively while only 17 objects showed short-term variability in both W 1 and W 2 bands. We also estimated the duty cycle (DC; see Rakshit et al 2017b) i.e. the fraction of time when an object is variable in Table 1.…”
Section: Short-term Variability Amplitudementioning
confidence: 99%
“…The outburst during 2016-2017 was reported and studied before (Rakshit et al 2017;Siejkowski & Wierzcholska 2017;Komossa et al 2017), and it was explained as the post-effect of secondary black hole impacted on disc (Valtonen et al 2017;Kushwaha et al 2018;Gupta et al 2019;Komossa et al 2020Komossa et al , 2021 or combination of shock and the jet's precession (Kapanadze et al 2018). In this section, we discuss the three origins of the outburst, including jet's precession, post-effect of black hole-disc impaction and TDE.…”
Section: Discussionmentioning
confidence: 82%
“…In addition to flux variations in the optical band (Rakshit et al 2017;Paliya et al 2017b), it has also shown polarization variations (Rakshit et al 2017). Flux variations are also seen in the GeV γ-ray energy band (Agudo et al 2011).…”
Section: Oj 287mentioning
confidence: 99%
“…One of the defining characteristics of blazars is that they show rapid flux variations over the complete accessible electromagnetic spectrum on a wide range of time scales from minutes to years. In addition to flux variability, they are strongly polarized and also show polar-E-mail: bhoomika@iiap.res.in ization variations (Kinman et al 1966;Angel & Stockman 1980;Andruchow et al 2005;Rakshit et al 2017). They have a compact radio structure often with core jet morphology, flat radio spectra and also show superluminal motion (Wagner & Witzel 1995;Ulrich et al 1997;Falomo et al 2014;Madejski & Sikora 2016).…”
Section: Introductionmentioning
confidence: 99%